Connecting with the community—experiences of medical students doing homestays in rural South Africa - Gaede, Bernhard (Frontiers in Medicine, 2025)
IntroductionThis study explores the educational and personal experiences of final-year medical students at the University of KwaZulu-Natal who participated in a homestay program during a seven-week rural clinical attachment. The initiative aimed to deepen students’ understanding of the social determinants of health by immersing them in the communities they served, moving beyond traditional hospital-based training.MethodsStudents were invited to participate in the homestay project, prior to their rural clinical attachment. The study draws on qualitative data from focus group discussions and interviews with participating students, exploring their experiences during the homestays. The transcripts were thematically analysed using a framework analysis approach.ResultsThe research highlights how living with host families in deep rural areas fostered cultural humility, empathy, and a holistic view of care. Students reported that the homestay experience humanized their clinical practice, allowing them to perceive patients as individuals embedded within complex social and cultural contexts. Many described transformative learning moments, such as navigating cultural differences and traditional healing practices, and understanding the challenges of health care in rural communities. Despite challenges—including transport issues, food adaptation, and navigating gender norms—students overwhelmingly found the experience enriching and stress-reducing, with strong relational bonds formed between them and their host families.DiscussionThe study situates these findings within broader discourses on decentralized health professions education (HPE), arguing that authentic, relational learning in community settings can challenge hierarchical and urban-centric models of medical training. The homestay model facilitated a shift in educational space—from controlled clinical environments to complex, lived community contexts—enhancing students’ professional identity formation and responsiveness to rural health needs. The process of place-making seems to be key in shaping meaning making and transformational change. The homestay project demonstrated the potential of community immersion to transform medical education by fostering empathy, cultural understanding, and a deeper, authentic connection to the lived realities of patients in shaping socially accountable health professionals.